2010
DOI: 10.1080/15562941003792119
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Pap Test Utilization Among Legal Permanent Resident Women

Abstract: The Office of Minority Health (OMH) notes an increase in health disparities in the minority population (OMH, 2008). This study examines the factors that determine access to Pap test utilization among recent immigrant women who hold legal permanent status using the first wave of data from the New Immigrant Survey. Using the behavioral model of health services for vulnerable populations, we work to determine the variables that contribute to immigrant women's health service utilization or the Pap test. In order t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
(28 reference statements)
0
1
0
Order By: Relevance
“…These sorts of practices are outside the control of the refugee women seeking care. Kagotho and Pandey found that cultural practices and the health care system in the country of origin influence the health‐seeking behaviours of individuals, when in a new country. Health services need to consider the needs of those seeking care, including ethnic‐specific needs, which have been shown to contribute to inequality in cervical and breast cancer screening programs .…”
Section: Discussionmentioning
confidence: 99%
“…These sorts of practices are outside the control of the refugee women seeking care. Kagotho and Pandey found that cultural practices and the health care system in the country of origin influence the health‐seeking behaviours of individuals, when in a new country. Health services need to consider the needs of those seeking care, including ethnic‐specific needs, which have been shown to contribute to inequality in cervical and breast cancer screening programs .…”
Section: Discussionmentioning
confidence: 99%